Pengembangan Model Supply Chain Pangan Berbasis Matematika di Nusa Tenggara Barat - Afriansyah, Dilla; Perdhana, Firman Fajar; Dwikasari, Lingga Gita; Sukma, Dinda Galuh (FKIP Universitas Mataram, 2025)
The food supply chain in West Nusa Tenggara (NTB) faces several challenges, including poor transportation infrastructure, high distribution costs, and post-harvest losses. This study aims to design a mathematical model based on Linear Programming (LP) to improve the efficiency of the food supply chain in the region. The findings reveal that investments in transportation infrastructure, post-harvest technology, and technology-based information systems can significantly reduce distribution costs by 15%, decrease post-harvest losses by 25%, and enhance price stability. This model provides practical solutions to optimize food distribution and supports sustainable food security policies.